Food Diversification of Moringa Plants into Chips as a Healthy Snack for the Community - Andi Asmawati; Hilda Karim; Muhammad Juanda; Evi Ristiana; Faidhul Inayah (PT. Global Research Collaboration, 2024)
Moringa-based food product development can provide significant nutritional and economic benefits to the community. The manufacturing process includes plucking and boiling moringa leaves, followed by mashing together garlic and shallots. The dough is mixed with wheat flour, starch, margarine, eggs, and moringa water, then kneaded until evenly distributed. Moringa noodles are molded according to taste using a noodle maker, then fried in hot oil until golden brown. Once cooled, packaged. This opportunity not only increases the nutritional value of food products, but also provides great economic potential for local farmers and housewive.